Investigation of the expansin gene family in sugar beet (Beta vulgaris) by the genome-wide level and their expression responses under abiotic stresses - Faris Abdulkhadum Al-Mamoorı, Dima; Celik Altunoglu, Yasemin; Horuz, Erdoğan; Özkan Kök, Büşra (Springer Science and Business Media LLC, 2023)
Sugar beet (Beta vulgaris ssp. vulgaris) is primarily used in sugar production worldwide. Expansins are a gene family of cell wall proteins effective in regulating cell wall structure. They also participate in developmental stages, including cell and leaf growth, root development, and fruit ripening. This study comprehensively characterizes the expansin gene family members found in the sugar beet genome. In addition, in silico expression analysis of sugar beet expansin genes under variable abiotic stress conditions and expression profiles of expansin genes under combined drought and heat stresses by the qRT-PCR method were evaluated in the study. A total of 31 sugar beet expansin genes were identified. BvuEXLA-02 and BvuEXLB-02 genes can have abiotic stress tolerance roles besides their roles in normal development. Determining the properties of sugar beet expansin, family members can help enable the cellulose hydrolysis mechanism and raise plant biomass. Elucidating expression profiles of the sugar beet expansin genes under variable stress conditions can support improving plant productivity. The results of the current study may also contribute to the deep understanding of sugar beet expansin genes in the future.
Keywords: QK Botany / növénytan; 2. Zero hunger